PENGARUH SISTEM VESSEL TRAFFIC SERVICES (VTS) TERHADAP STASIUN RADIO PANTAI (SROP) DALAM PELAYANAN TELEKOMUNIKASI KEDATANGAN KAPAL DI WILAYAH PELABUHAN TANJUNG PERAK SURABAYA - Naila Andin Tazkiya Gian Nafisah; Sianturi, Intan; Ratnaningsih, Dyah; Dahri, Muh (UNIMAR AMNI Semarang, 2025)
Vessel Traffic Services (VTS) is an expansion of the Coast Radio Station (SROP) function in the field of shipping telecommunications in the Navigation District. However, its presence makes the function of the Coast Radio Station (SROP) limited. This was observed by the author when carrying out land practices which were then researched in this scientific work. The purpose of this study is to identify whether the Vessel Traffic Services (VTS) function can affect the Shore Radio Station (SROP). There are 30 Vessel Traffic Services (VTS) installation operators and the Surabaya Coastal Radio Station (SROP) as population, sample and respondents. This study uses a quantitative approach to data collection methods in the form of observation field data, interviews, and questionnaires with simple regression analysis data analysis techniques. The results of the test show a significant effect because tcount> ttable or 4.1806 < 2.048 which indicates the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. The direction of the positive t value corresponds to the calculated correlation coefficient (r ≈ 0.6199), indicating that the correlation is positive.